(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
This paper discusses the Taganka Theatre’s production of Pasternak’s Doctor Zhivago, staged in a remote Moscow suburb. Performed in a Soviet-built palace of culture, the show radically reinterpretsZhivago, transforming it from an intensely personal to a collective narrative. Drawing on a chapter from my book Theatre in Passing: A Moscow Photo-Diary (Intellect 2011), the paper refers to Marvin Carlson, who argues that theatre buildings and their locations greatly impact the overall meaning of a show. Citing evidence provided by cultural theorists, architectural critics, as well as authors and artists, I expand on my earlier discussion of suburbs – a fertile subject attracting a wealth of contradictory opinions. I illustrate my discussion with images of high-rises inspired by the avant-garde photographer Alexander Rodchenko, and pictures of soup cans and cases of Coca-Cola – my tribute to Andy Warhol, who, like Rodchenko, rejected the old in favour of the new. I conclude with a nostalgic shot of a single-family dwelling, reminiscent of the spaces depicted in Pasternak.